Staying safe from pitfalls in primary knee replacements - Rajkumar Gangadharan; Srinivas B S. Kambhampati; Jagdish Menon (Apollo Medicine)
With increasing numbers of primary knee replacements and the growing concerns of revision knee replacements, research is now tending to look back and look forward for all that is possible to reduce the complications and improve patient satisfaction in this highly successful surgery. The clinician must make a comprehensive assessment of the patient, identify the real needs and optimize the risks of this major surgery, against real benefits. This article reviews relevant aspects of preoperative, intraoperative, and postoperative care that practically influence a successful outcome that every potential candidate for knee replacement rightfully deserves.